MENGUKUR PERFORMANSI REFRIGERATOR ALAMI DENGAN MODIFIKASI BERBENTUK DISPENSER - , RONY MUHAMMAD; , Dr.Eng. M. Kholid Ridwan, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to measuring the performance of the natural refrigerator that loaded with water and has been modified in dispenser form. This dispenser made based on modified of natural refrigerator created by Emily Cummins, a woman from England. This dispenser has outer shell in the form of ceramics that pierced in the some points, and inner shell in the form of aluminum. Empty space between ceramics and aluminum filled with river sand. Water gallon added in the top of the aluminum and a faucet added in the bottom of so it can be functioned like dispenser. Procedure to measuring the performance of the dispenser is using a thermometer data logger that has 2 water temperature sensors that each of them used to measuring water temperature inside and outside of dispenser. The data that obtained from those thermometer sensors saved in the time interval of 10 minutes. And then his data compared and analyzed until it get estimation of performance from this model of dispenser. xvii The result of this research showed that design of this dispenser can make the temperature of water inside this dispenser reducing and lower than temperature of water outside this dispenser.